Auditors’ Perception towards Time Schedule Pressure and Reduced Audit Quality Practices: A Study from Bangladeshi Context - Neogy, Taposh Kumar; Hossain, Md. Shakawat (Asian Accounting and Auditing Advancement, 2012)
Research on Reduced Audit Quality Practices (RAQP) has consistently shown the serious negative consequences of this practice in the auditing profession. However, research in RAQP is relatively few in emerging or newly industrialized countries, and much of the relevant literature is derived from developed countries. Therefore, this study examines the effect of time budget pressure on RAQP in the context of a developing country, Bangladesh. Based on a mailed questionnaire survey to the auditors, the results suggest that RAQP does occur in Bangladesh audit firms, particularly in non-big four firms.